"Am I safe?". Issue 5 (16th September 2021) - Vanderford, Paula
Abstract: John's mother had insisted that no health care providers tell him he was dying. He was fourteen, with metastases in his lungs, and I was in the position of being the doctor who would extubate him to bilevel positive airway pressure with the goals of providing comfort and getting him home. He would not be reintubated if the BIPAP failed. It was unclear what John knew or understood. Did he know that the experimental treatment was not working and that he was dying? He clearly wanted the endotracheal tube to be removed. It was unclear whether he understood that this action might result in him dying more quickly .